2019
DOI: 10.1101/539114
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Local Targeted Memory Reactivation in Human Sleep

Abstract: Memory consolidation can be promoted via Targeted Memory Reactivation (TMR)that re-presents training cues or context during sleep. Whether TMR acts locally or globally on cortical sleep oscillations remains unknown. Here we exploit the unique functional neuroanatomy of olfaction with its ipsilateral stimulus processing to perform local TMR in one brain hemisphere. Participants learned associations between words and locations in left or right visual fields with contextual odor throughout. During post-learning n… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 63 publications
2
16
1
Order By: Relevance
“…These sensory cues are then replayed during sleep with memory performance being assessed in sensory cued versus un-cued trials in subsequent waking periods. These studies have shown that sensory cueing specifically during SWS enhances slow wave-sleep spindle coupling and memory performance ( Rasch et al, 2007 ; Rudoy et al, 2009 ; Antony et al, 2012 ; Van Dongen et al, 2012 ; Feld and Diekelmann, 2015 ; Batterink et al, 2016 ; Berkers et al, 2018 ; Bar et al, 2020 ), with the efficacy of this effect depending on the phase of the slow wave during sensory cueing ( Batterink et al, 2016 ; Goldi et al, 2019 ). Hence, these findings implicate a mechanism by which triple coupling of SO, sleep spindle, and ripple events coordinate replay of relevant neuronal ensembles supporting targeted neuroplasticity in facilitation of memory consolidation.…”
Section: Local Sleep and Ad-related Memory Impairmentmentioning
confidence: 99%
“…These sensory cues are then replayed during sleep with memory performance being assessed in sensory cued versus un-cued trials in subsequent waking periods. These studies have shown that sensory cueing specifically during SWS enhances slow wave-sleep spindle coupling and memory performance ( Rasch et al, 2007 ; Rudoy et al, 2009 ; Antony et al, 2012 ; Van Dongen et al, 2012 ; Feld and Diekelmann, 2015 ; Batterink et al, 2016 ; Berkers et al, 2018 ; Bar et al, 2020 ), with the efficacy of this effect depending on the phase of the slow wave during sensory cueing ( Batterink et al, 2016 ; Goldi et al, 2019 ). Hence, these findings implicate a mechanism by which triple coupling of SO, sleep spindle, and ripple events coordinate replay of relevant neuronal ensembles supporting targeted neuroplasticity in facilitation of memory consolidation.…”
Section: Local Sleep and Ad-related Memory Impairmentmentioning
confidence: 99%
“…A recent study demonstrated that causal interventions affecting memory consolidation may also be applied locally. Unilateral olfactory stimulation induced “local targeted memory reactivation” and elicited both behavioral and EEG effects that were largely lateralized to one hemisphere (see preprint at - Bar et al, 2019). Such lateralization seems more difficult to demonstrate in the auditory modality (Simor et al, 2018), possibly because cortical auditory processing is less lateralized compared to vision and olfaction (Schnupp et al, 2011).…”
Section: How Can We Improve Causal Interventions In Humans Linking Slmentioning
confidence: 99%
“…Another study employed simultaneous EEG-fMRI and found univariate signal increases in learning-related areas during spindles 44 (see also 44 ), but it remained open whether such reactivation bears relevance for memory consolidation. Finally, the advent of targeted memory reactivation (TMR) protocols 45,46 has shown evidence for both SO-spindle complexes and information processing in response to external reminders 32,34,[47][48][49][50][51] , but it is unclear whether and how such exogenous memory reactivation relates to endogenous reactivation in service of memory consolidation. In sum, different lines of research across species point to a key role in coupled sleep oscillations, but the dynamics of endogenous reactivation in humans and its relevance for memory consolidation has remained unclear.…”
Section: Discussionmentioning
confidence: 99%